Optical coherence tomography angiography analysis of foveal microvascular changes and inner retinal layer thinning in patients with diabetes. Issue 9 (19th December 2017) - Kim, Kiyoung; Kim, Eung Suk; Yu, Seung-Young
Abstract : Aim: To evaluate the correlation between inner retinal layer thinning and the foveal microvasculature in type 2 diabetes using optical coherence tomography angiography (OCTA). Methods: A cross-sectional study involved 155 diabetic eyes. All patients were divided into two groups based on diabetic retinopathy (DR) grade: no DR (NDR, n=80) and mild-to-moderate non-proliferative DR (NPDR, n=75). Foveal avascular zone (FAZ) area, FAZ circularity index, FAZ perimeter, vessel density and perfusion index of parafoveal and perifoveal area were calculated using OCTA. The thickness of the macular ganglion cell/inner plexiform layer (mGCIPL) was measured using OCT. Results: In both superficial and deep retinal capillary layers (SRL and DRL), FAZ areas in the NDR (0.38 mm 2, 0.49 mm 2 ) and NPDR (0.38 mm 2, 0.48 mm 2 ) were greater than those in the control (0.33 mm 2, 0.43 mm 2 ). The FAZ circularity index, vessel density and perfusion index in the NDR (0.63, 17.8/mm, 0.32) and NPDR (0.63, 17.5/mm, 0.32) were smaller than those in the control (0.69, 19.6/mm, 0.39). mGCIPL thickness was significantly correlated with FAZ area in the SRL and DRL, as well as with FAZ circularity index, vessel density and perfusion index in the NDR and NPDR. In multivariate regression analysis, the FAZ circularity index (OR=12.2) and vessel density of the parafovea (OR=1.95) were correlated with mGCIPL thinning. Conclusion: OCTA revealed that early foveal microcirculatory alterations in diabetic eyes were related to mGCIPL thickness, regardless of the presence of DR. The decrease in FAZ circularity and parafoveal vessel density were highly correlated with mGCIPL thinning.